EVALUASI PROGRAM IMPLEMENTASI PENDEKATAN BEYOND CENTERS AND CIRCLE TIME (BCCT) - OKTARIA, RENTI (Program Studi Magister Pendidikan Anak Usia Dini, 2014)
Abstract: The evaluation research aimed to acknowledging the effectiveness ofthe implementationof beyond centers and circle time approach at RA Istiqlal Jakarta Pusat in 2014. The evaluationresearch is selected as a research method, use the CIPP Model from Daniel Stufflebeam. Theresearch were use multi technique and instrumen to collect the data and analizying data use thedesciptive statistic and qualitative technique. The result of research give a conclusion that theimplementation of beyond centers and circle time approach at RA Istiqlal Jakarta Pusat in 2014has been effective. It was seem that (1) RA Istiqlal Jakarta has been the curriculum and handbookof beyond centers and circle time; (2) There are 20 teachers average graduation of S-1 and theyreceived basic training of BCCT and communication skill; (3) There are 10 centers consist ofibadah, natural materials, macro dramatic play, micro dramatic play, block, readiness,movement, creative art, music, and cooking; (4) Child classified by age group with a ratio 12 2that 12 students with 2 teachers; (5) Teacher have implemented scaffolding the environment,scaffolding the pre-play experience, scaffolding the individual child’s play experience, andscaffolding the post play experience; (6) High quality play environments for children support thethree kinds ofplay. Keywords:Evaluation Program, Beyond Centers and Circle Time,Early Childhood Education. Abstrak: Studi evaluasi ini bertujuan untuk mengetahui efektivitas dari pelaksanaan pendekatanbeyond centers and circle time(BCCT) di RA Istiqlal Jakarta Pusat tahun 201 4. Metode penelitianyang digunakan adalah evaluasi dengan model CIPP dari Daniel Stufflebeam. Teknikpengumpulan data menggunakan observasi, wawancara, dan angket.Analisis data menggunakandeskripsi. Hasil penelitian adalah implementasi pendekatan BCCT di RA Istiqlal Jakarta tahun201 4 berjalan efektif, yakni: (1 ) RA Istiqlal Jakarta memiliki kurikulum dan panduan BCCT; (2)Ada 20 orang guru lulusan S1 dan mendapatkan pelatihan dasar BCCT dan keterampilankomunikasi; (3) Ada 1 0 sentra yang terdiri dari sentra ibadah, bahan alam, main peran makro,main peran mikro, balok, persiapan, olah tubuh, seni kreativitas, musik dan memasak; (4) Muriddiklasifikasi berdasarkan kelompok usia dengan rasio 1 2 orang anak dengan 2 orang guru; (5)Guru telah melaksanakan pijakan penataan lingkungan, pijakan pengalaman sebelum main,pijakan pengalaman main setiap anak, dan pijakan pengalaman setelah main; dan (6) 3 jenis maindidukung dengan adanya lingkungan main yang berkualitas untuk murid. Kata kunci: Evaluasi Program, Beyond Centers and Circle Time, PAUD.